2016
DOI: 10.7882/az.2015.022
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of Honeyeaters (Meliphagidae) in Western Australian Eucalypt Woodlands I: Resource Allocation Among Species in the Great Western Woodland During Spring

Abstract: Nectar-feeding birds are commonly the most abundant birds in Australian eucalypt forests and woodlands, where they play a key role as pollinators of native plants. Among the nectar-feeders, honeyeaters (Meliphagidae) are particularly aggressive and may exclude other birds from the habitats they occupy thereby affecting the composition of avian communities and the distribution of species on a landscape scale. Such behaviour has cascading effects on ecosystems, changing the abundances and kinds of planteating ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…The specialist has been supported by its special characteristics in the form of a long and sturdy beak to pick up nectar on a large or deep flower crown like Bombax ceiba and insects on the bark of trees. Honeyeaters select flowers by size and sturdiness of available perches such as Eucalyptus spp., feed on large inflorescences (Recher and Davis 2011), which flowered more abundantly, had cup-shaped flowers (Recher et al 2016). This is in line with Scoble and Clarke (2006), that nectarivorous birds (family Meliphagidae) prefer flowers that contain large amounts of nectar.…”
Section: Discussionmentioning
confidence: 68%
“…The specialist has been supported by its special characteristics in the form of a long and sturdy beak to pick up nectar on a large or deep flower crown like Bombax ceiba and insects on the bark of trees. Honeyeaters select flowers by size and sturdiness of available perches such as Eucalyptus spp., feed on large inflorescences (Recher and Davis 2011), which flowered more abundantly, had cup-shaped flowers (Recher et al 2016). This is in line with Scoble and Clarke (2006), that nectarivorous birds (family Meliphagidae) prefer flowers that contain large amounts of nectar.…”
Section: Discussionmentioning
confidence: 68%
“…The most reported is the New Holland honeyeater (Phylidonyris novae-hollandiae) with 142 plant species. Honeyeaters have diverse foraging preferences and diets, and they can feed primarily on nectar or other foods depending on species, habitats and timing (Collins and Briffa 1982;Recher and Davis 2011;Low 2014) Nectar-feeding birds can be nomadic to exploit unreliable resources in dry areas (Main 1981). Some bird-flower associations are less specialised in Australia, because birds such as silvereyes and some parrots are casual pollinators and other birds that visit flowers may be feeding primarily on insects (Anderson et al 2016).…”
Section: E R I O C H I L U S D I L a T A T U S P Y R O R C H I S N I ...mentioning
confidence: 99%
“…among butterfly groups in renosterveld scrublands, Cape Region) (Topp et al, 2022). Regarding bird pollinators, research in the Cape Region and Australia has shown that non‐migratory, exclusive nectar consumers, which normally are active throughout the year in the same area, can suffer severe impacts if the density of post‐fire intact patches of nectar‐providing bushes falls below certain thresholds (Geerts et al, 2020; Recher & Davis Jr., 2011). The differential responses of pollinator groups to fire traits suggest a need for caution in invoking the intermediate disturbance hypothesis, especially when natural fire patterns are altered (Box 3).…”
Section: Stressors On P–p Communitiesmentioning
confidence: 99%